Pemanfaatan E-Commerce dan Kesiapan Modal dalam Peningkatan Daya Saing Usaha Mikro, Kecil dan Menengah (UMKM) di Kecamatan Sunggal, Deli Serdang - Anton Sihombing; Novena Putri Antonia Sihombing (Universitas Methodist Indonesia, 2025)
This study aims to analyze the influence of e-commerce utilization and capital readiness on enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Sunggal District, Deli Serdang Regency. The research is motivated by the low competitiveness of MSMEs, which is primarily due to limited adoption of digital technology and weak capital structures. The study adopts a quantitative approach with an associative research design. A total of 70 MSME actors were selected through a census using purposive sampling techniques. Data collection was carried out through questionnaires, and the data were analyzed using multiple linear regression. The results indicate that e-commerce utilization has a positive and significant effect on MSME competitiveness, with a regression coefficient of 0.592 and a significance level of < 0.05. Likewise, capital readiness also shows a positive and significant effect, with a regression coefficient of 0.272. Simultaneously, both variables exert a strong influence, with an F-statistic of 228.065 and a significance value of 0.000. The coefficient of determination (Adjusted R Square) is 0.868, indicating that 86.8% of the variance in competitiveness can be explained by e-commerce utilization and capital readiness. These findings underscore that digital transformation through e-commerce and capital strengthening are key strategies in improving MSME competitiveness. The study recommends digital training, enhanced financial literacy, facilitation of access to financing from financial institutions, and supportive government policies.